2020
DOI: 10.1523/eneuro.0319-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

DGKγ Knock-Out Mice Show Impairments in Cerebellar Motor Coordination, LTD, and the Dendritic Development of Purkinje Cells through the Activation of PKCγ

Abstract: Diacylglycerol kinase g (DGKg) regulates protein kinase C (PKC) activity by converting DG to phosphatidic acid (PA). DGKg directly interacts with PKCg and is phosphorylated by PKCg , resulting in the upregulation of lipid kinase activity. PKC dysfunction impairs motor coordination, indicating that the regulation of PKC activity is important for motor coordination. DGKg and PKC are abundantly expressed in cerebellar Purkinje cells. However, the physiological role of DGKg has not been elucidated. Therefore, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…However, the basal phosphorylation level of PKCα in tm1d mice was equivalent to that in tm1c mice ( Figure 3 a: tm1c, 1.00; tm1d, 1.00 ± 0.070). These results suggested that the upregulation of basal PKCγ activity in tm1d mice causes the impairment of motor coordination, similarly seen in the conventional DGKγ KO mice [ 15 ].…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…However, the basal phosphorylation level of PKCα in tm1d mice was equivalent to that in tm1c mice ( Figure 3 a: tm1c, 1.00; tm1d, 1.00 ± 0.070). These results suggested that the upregulation of basal PKCγ activity in tm1d mice causes the impairment of motor coordination, similarly seen in the conventional DGKγ KO mice [ 15 ].…”
Section: Resultsmentioning
confidence: 86%
“…We examined the DGKγ expression levels in the brain of tm1d mice using western blotting and found that the DGKγ expression was significantly decreased at 16 weeks old (about 50%) in the cerebellum but not in the cerebrum ( Figure 1 e). The reason why the expression did not disappear completely was due to DGKγ expression in the granule cells [ 15 ]. Thus, we tested the motor coordination of tm1d mice by the rotarod and beam tests.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations